Prevalence of psychiatric ailments among patients with sexually transmitted disease - Mandal, MC; Mullick, SI; Nahar, JS; Khanum, M; Lahiry, S; Islam, MA (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S23-27The abstract of this article is available on the PubMed website